Epigenetic Mechanisms for the Early Environmental Regulation of Hippocampal Glucocorticoid Receptor Gene Expression in Rodents and Humans - Zhang, Tie Yuan; Labonté, Benoit; Wen, Xiang Lan; Turecki, Gustavo; Meaney, Michael J (Neuropsychopharmacology (New York, N.Y.), 2013)
Parental care influences development across mammals. In humans such influences include effects on phenotypes, such as stress reactivity, which determine individual differences in the vulnerability for affective disorders. Thus, the adult offspring of rat mothers that show an increased frequency of pup licking/grooming (ie, high LG mothers) show increased hippocampal glucocorticoid receptor (GR) expression and more modest hypothalamic-pituitary-adrenal responses to stress compared with the offspring of low LG mothers. In humans, childhood maltreatment associates decreased hippocampal GR expression and increased stress responses in adulthood. We review the evidence suggesting that such effects are mediated by epigenetic mechanisms, including DNA methylation and hydroxymethylation across GR promoter regions. We also present new findings revealing associated histone post-translational modifications of a critical GR promoter in rat hippocampus. Taken together these existing evidences are consistent with the idea that parental influences establish stable phenotypic variation in the offspring through effects on intracellular signaling pathways that regulate the epigenetic state and function of specific regions of the genome.